FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI PERAWAT DALAM MELAKUKAN PENDOKUMENTASIAN KEPERAWATAN DI RUANG MEDIKAL BEDAH RUMAH SAKIT PLUIT JAKARTA - - Marni (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2013)
This study backs on the importance of dilator nursing documentation as a tool of responsibility and accountability of nurses in nursing care. To do the documentation needed motivation. The purpose of this study was to determine the factors that influence the motivation of nurses in the conduct of nursing documentation. The research was conducted in Jakarta Pluit Hospital, in two units of the treatment room, the floor of V and VIIfloor, with a total sample of 33 respondents and 33 copies of client files. The sampled respondents are nurses who have met the sample criteria. Research instruments used were questionnaires with closed-form questions, observation guidelines. The process of data collection is done by distributing questionnaires to the respondents, respondents made observations of nursing documentation. This study uses quantitative methods through deskriptik analytic approach with cross-sectional design. Time data collection from 20 October 2003 to 3 November 2003. The results using the method of analysis of Spearman's rho correlation coefficient data obtained as follows: there is a relationship between the means of the completeness of the documentation, there is a relationship between the attitude of nurses to the completeness of the documentation. As for supervision, nursing personnel, policy and institutional knowledge there will be no relationship (there is a very weak relationship) with the implementation documentation.Keywords: motivation, nursing documentation